Development of Digital Marketing Strategy and Service Quality Using Social Media Towards Digital Economy - Koesharijadi Koesharijadi; Anak Agung Alit Merthayasa; Ikhsan Nendi (Syntax Corporation Indonesia, 2022)
Technological advances have had an impact on shifting monotonous advertising and marketing techniques in digital marketing. In addition, digital marketing is firm in impacting the digital economy to help revive the economy. Based on the needs and changes in people's lifestyles, this study aims to examine the development of digital marketing strategies and service quality through the role of social media in the digital economy. This type of research is qualitative with a literature review method with data sources obtained through reference books and articles in the google scholar database. The results of this study include that social media should be considered an inseparable part of the integrated marketing strategy of the organization and should not be taken lightly. Social media is an alternative and proper strategy to use as an online advertising medium. Social media, as a digital marketing strategy development, has an essential role in helping market products so that they also impact the economy. Employee involvement in marketing will impact the services provided to consumers. The services provided have an impact on consumers' assessment of the good and bad of the company. The role of the company's social media sites in monitoring target market users is another critical factor in ensuring the success of digital marketing